Kostas A. Lavdas, The Europeanization of Greece: Interest Politics and the Crises of Integration - Χ., Σ. (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2015)
[Δεν διατίθεται περίληψη / no abstract available]